Meningkatkan Aksesebilitas Informasi dan Literasi Pengguna Melalui Aplikasi E-Library UIN Raden Fatah: - Lisa Agustina Soraya Ripmiatun; Rohmaniyah (Perpustakaan Universitas Riau, 2024)
Increasing access to information and literacy through the UIN Raden Fatah Palembang e-library application is a very important effort to improve the quality of education and increase students' ability to access relevant and accurate information. In this context, the e-library application developed by UIN Raden Fatah Palembang has great potential in increasing access to information and literacy among students and lecturers. Apart from that, this application is also equipped with features that help improve literacy, such as searching for books using bar-codes and others, as well as the ability to search and organize information. In this research, the author will evaluate the effectiveness of the UIN Raden Fatah Palembang e-library application in increasing access to information and literacy among students and lecturers. The author will also examine how this application can help improve students' abilities in accessing relevant and accurate information, as well as how this application can help improve lecturers' abilities in teaching and providing guidance. The research aims to analyze and document how the implementation of the e-library application at UIN Raden Fatah Palembang has increased information accessibility and user literacy. In the context of the digital era, the existence of e-library applications is important in enabling users to access and utilize information effectively via mobile devices. The method used by the author in this research is descriptive qualitative which acts as a reference in making this article, because the author took many sources from previous research as well as observation results on the UIN Raden Fatah Palembang e-library application. It is hoped that the results of this research can contribute to the development of e-library applications that are more effective and efficient in increasing access to information and literacy among students and lecturers.